ANALISIS FAKTOR YANG MEMENGARUHI KINERJA PENGADAAN BARANG/JASA DALAM KEADAAN DARURAT WABAH COVID-19 DENGAN SOCIAL DISTANCING SEBAGAI VARIABEL MODERATOR - Syahirul Alim (Kementerian Keuangan); Muhammad Heru Akhmadi (Politeknik Keuangan Negara STAN) (Jurnal Manajemen Industri dan Logistik, 2021)
AbstractThe purpose of this study was to analyze the factors affecting the performance of the procurement of goods/services in the emergency of the Covid-19 plague with the addition of social distancing as a moderator variable. The study was conducted at the provincial government of DKI Jakarta. It was purposely selected due to the fact that the government has a sound procurement system. The general objective of the study was to analyze the factors that affect procurement performance in government organizations and the effect of social distancing on that relationship in the emergency situation during the Covid-19 plague. The specific objective of the study was; to determine the effect of government regulation for emergency procurement, e-procurement implementation employee competency, and management's commitment to the procurement performance during an emergency situation. This entailed the use of questionaries. The key finding of the study indicated that government regulation for an emergency situation, employee competency, and implementation of e-procurement positively affected procurement performance in the emergency situation of the Covid-19 plague. Furthermore, the study found that social distancing did not affect the relationship between the above-mentioned factors and procurement performance during an emergency situation.AbstrakPenelitian ini menganalisis faktor-faktor yang mempengaruhi kinerja pengadaan barang dan jasa dalam keadaan darurat wabah Covid-19 dengan menggunakan social distancing sebagai variabel moderator. Penelitian dilakukan di Pemprov DKI Jakarta sebagai organisasi yang telah memiliki sistem pengadaan yang baik melalui data kuesioner. Tujuan khusus dari penelitian ini adalah untuk mengetahui pengaruh peraturan pemerintah dalam pengadaan darurat, penerapan e-procurement, kompetensi pegawai, dan komitmen manajemen terhadap kinerja pengadaan pada saat keadaan darurat. Hasil penelitian menunjukkan bahwa regulasi pemerintah untuk situasi darurat, kompetensi pegawai, dan implementasi e-procurement berpengaruh positif terhadap kinerja pengadaan dalam situasi darurat wabah Covid-19. Sebagai tambahan, hasil penelitian juga menunjukkan bahwa variabel social distancing tidak memoderasi pengaruh empat faktor terhadap kinerja pengadaan barang dan jasa. Penggunaan teknologi informasi memungkinkan komunikasi dalam penyelesaian tugas tetap terjaga sehingga kinerja pengadaan barang dan jasa tidak terganggu selama pandemic Covid-19.